2005
DOI: 10.1007/s00359-005-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine, GABA and glutamate induce ionic currents in cultured antennal lobe neurons of the honeybee, Apis mellifera

Abstract: The honeybee, Apis mellifera, is a valuable model system for the study of olfactory coding and its learning and memory capabilities. In order to understand the synaptic organisation of olfactory information processing, the transmitter receptors of the antennal lobe need to be characterized. Using whole-cell patch-clamp recordings, we analysed the ligand-gated ionic currents of antennal lobe neurons in primary cell culture. Pressure applications of acetylcholine (ACh), gamma-amino butyric acid (GABA) or glutama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 128 publications
10
96
0
Order By: Relevance
“…However, similar observations were described in previous reports on pupal honeybee AL cells (Barbara et al 2005) and this apparent discrepancy could result from the activity of Na…”
Section: Relative Ion Permeabilitiessupporting
confidence: 84%
See 2 more Smart Citations
“…However, similar observations were described in previous reports on pupal honeybee AL cells (Barbara et al 2005) and this apparent discrepancy could result from the activity of Na…”
Section: Relative Ion Permeabilitiessupporting
confidence: 84%
“…Native neuronal ionotropic chlorideselective GABA receptors have been studied in several insect species such as fruitfly (Lee et al 2003;Su and O'Dowd 2003), cockroach (Alix et al 2002;Ihara et al 2005;Le Corronc and Hue 1999;Zhao et al 2003), cricket (Cayre et al 1999), sphinx moth (Sattelle et al 2003), and honeybee (Barbara et al 2005;Grünewald and Wersing 2008). Electrophysiological techniques and radioligand-binding assays have been used to compare the pharmacological profile of insect and vertebrate ionotropic GABA receptors, demonstrating that insect GABA receptors differ pharmacologically from their vertebrate counterparts (for review see .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In honey bees, the neonicotinoid imidacloprid inhibits receptors for -aminobutyric acid (GABA), a major neurotransmitter in the central nervous system (Thany, 2010). Imidacloprid is a partial agonist of nAChRs in brain areas associated with olfaction, learning and memory: cultured antennal lobe neurons (Barbara et al, 2005;Barbara et al, 2008) and cultured Kenyon cells from mushroom bodies (Déglise et al, 2002). Suchail et al found that imidacloprid is metabolized relatively quickly and has a half-life of 4-5h (Suchail et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, glutamate immunoreactivity, the localization of glutamate receptors and the recording of inhibitory and excitatory glutamate-induced currents, suggests the existence of a glutamate neurotransmission in the insect CNS (Ultsch et al, 1992;Cully et al, 1996;Barbara et al, 2005;Featherstone et al, 2005;Xia et al, 2005;Zannat et al, 2006;Devaud et al, 2008). In addition, several studies in the honeybee suggest that this neurotransmission is implicated in memory formation, but it is not known how it integrates the neural networks of olfactory coding and learning (Si et al, 2004;Locatelli et al, 2005;Kucharski et al, 2007;El Hassani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%